The safety and efficacy of modified minimally invasive trabeculectomy for the treatment of primary chronic angle-closure glaucoma - WuZhenggen; HuangChukai; ZhengCe; HuangYuqiang; ZhangWanqi; MaDi (眼科学报, 2015)
Background: Primary chronic angle-closure glaucoma (PCACG) is one of the main types of glaucoma in China. Trabeculectomy is the most commonly used glaucoma filtration surgery for glaucoma in the world. Conventional trabeculectomy is prone to anesthesia-related complications intraoperative and operation-related complications postoperative in PCACG treatment. Modified minimally invasive trabeculectomy maybe can reduce the incidence of complications. Methods: We conducted a prospective case series study and performed modified fornix-based trabeculectomy in 27 patients (30 eyes) under topical anesthesia; we then observed intraoperative anesthesia and cooperation effect, intraoperative and postoperative complications, preoperative and postoperative visual acuity, intraocular pressure (IOP), visual field, and the use of ocular hypotensive drugs. The patients were followed up for at least 12 months. Results: All operations were completed successfully with no intraoperative complications. All 27 patients (30 eyes) were followed up for at least 12 months. No significant decrease in visual acuity was observed at days 1 or 7 and at months 1, 3, 6, and 12 after operation; however, a significant decrease in IOP was observed at days 1 and 7 and at months 1, 3, 6, and 12 after operation. Moreover, no significant progression in visual field mean defect was observed at month 12 after operation, and the number of ocular hypotensive drugs required was significantly reduced at months 6 and 12 after operation. By month 12 after operation, the overall success rate was 93.33% (28/30). Conclusions: Modified minimally invasive trabeculectomy is safe and effective for the treatment of PCACG.